2006
DOI: 10.1152/ajpcell.00397.2005
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CaM kinase II and phospholamban in SNP-induced relaxation of murine gastric fundus smooth muscles

Abstract: The mechanisms by which nitric oxide (NO) relaxes smooth muscles are unclear. The NO donor sodium nitroprusside (SNP) has been reported to increase the Ca2+ release frequency (Ca2+ sparks) through ryanodine receptors (RyRs) and activate spontaneous transient outward currents (STOCs), resulting in smooth muscle relaxation. Our findings that caffeine relaxes and hyperpolarizes murine gastric fundus smooth muscles and increases phospholamban (PLB) phosphorylation by Ca2+/calmodulin (CaM)-dependent protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
0
35
1
Order By: Relevance
“…In addition, autonomous CaM kinase II activity and PLB-Thr17 phosphorylation was increased, suggesting that CaM kinase II activation is mediated by localized Ca 2ϩ release events from the SR in murine gastric smooth muscles (19). Furthermore, the findings that PLB phosphorylation results in increased SERCA activity and increased SR Ca 2ϩ release suggest that PLB phosphorylation would exert a positive feedback effect on CaM kinase II, by maintaining enhanced SR Ca 2ϩ release (19,20,21). Similarly, PLB gene ablation would also be expected to elevate CaM kinase II activity by maintaining enhanced SR Ca 2ϩ uptake and release (32,43).…”
mentioning
confidence: 99%
“…In addition, autonomous CaM kinase II activity and PLB-Thr17 phosphorylation was increased, suggesting that CaM kinase II activation is mediated by localized Ca 2ϩ release events from the SR in murine gastric smooth muscles (19). Furthermore, the findings that PLB phosphorylation results in increased SERCA activity and increased SR Ca 2ϩ release suggest that PLB phosphorylation would exert a positive feedback effect on CaM kinase II, by maintaining enhanced SR Ca 2ϩ release (19,20,21). Similarly, PLB gene ablation would also be expected to elevate CaM kinase II activity by maintaining enhanced SR Ca 2ϩ uptake and release (32,43).…”
mentioning
confidence: 99%
“…Since these stimulators are known to inhibit slow wave and produce hyperpolarization, then suppressing contraction, it inhibits phasic contraction and basal tone in GI tract (Andersson and Nilsson, 1972;Jin et al, 1993;Smith et al, 1993). These findings imply that cyclic nucleotide activators such as FSK and SNP play an inhibitory role for basal tone as well as spontaneous contraction in human stomach (Huizinga et al, 1991;Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Kim et al, 2006;Kim and Perrino, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…β-Adrenergic nerve and VIP containing neurons in myenteric plexus, which project to the smooth muscle layers, have been reported to exist in the gut, and their stimulation inhibits slow wave and contraction via increasing cAMP and/or cGMP (Andersson and Nilsson, 1972;Jin et al, 1993;Smith et al, 1993). Furthermore, FSK and SNP, cyclic nucleotide (cAMP and cGMP) activators, have also been shown to inhibit electrical and contractile activity of GI smooth muscle (Huizinga et al, 1991;Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Kim et al, 2006;Severi et al, 2006). In the present study, we found the inhibitory effect of ISO in human stomach: ISO inhibited spontaneous contraction and basal tone in a reversible manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cardiac and slow-twitch skeletal muscles have long established that SERCA can be regulated by phospholamban (PLN), such that phosphorylation of PLN (e.g., by cyclic nucleotides) disinhibits SERCA (5,9,37). Although PLN expression and phosphorylation under physiological conditions have been demonstrated in gastrointestinal (27,28) and vascular smooth muscles (6,8,18,25,30,59), data on the role of PLN in ASM are very limited (38).…”
mentioning
confidence: 99%